Optimized workflow for paroxysmal atrial fibrillation ablation using very high power short duration - Gigli, Lorenzo; Preda, Alberto; Testoni, Alessio; Kotinas, Alexios Sotirios; Tacchetto, Andrea; Guarracini, Fabrizio; Carbonaro, Marco; Vargiu, Sara; Varrenti, Marisa; Colombo, Giulia; Menè, Roberto; Baroni, Matteo; et al. (Frontiers in Cardiovascular Medicine, 2025)
Backgroundwide antral pulmonary vein isolation (PVI) is effective for treating paroxysmal atrial fibrillation (PAF), although time-demanding. We investigated the impact of a standardized ablation protocol by using a bidirectional transeptal steerable sheath, high-density mapping and very high-power-short-duration (vHPSD) catheters on procedure timing, efficacy, and safety.Methodsconsecutive PAF patients free from previous ablations undergoing PVI alone between January 2022 and March 2023 were prospectively enrolled. The standardized workflow included general anesthesia, a single transeptal puncture trough with a bidirectional, steerable visualizable sheath introduced into the left atrium accommodated a high density, penta-spline mapping catheter and a contact force sensor ablation catheter enabled to deliver vHPSD. Procedural data and electrophysiology (EP) laboratory times were systematically collected and analyzed. The primary endpoint was any AF or atrial tachycardia recurrence at 12 and 24 month follow up.Resultsthe study cohort was composed by 138 patients (mean age was 59 ± 11 years, 38% female) and successful PVI was achieved in 100% of cases. Overall, first pass isolation (PFI) was 93%, with a LA dwell time of 32 ± 4 min. Significant complications were reported in 3% of patients. Skin-to-skin time and total EP laboratory time were 58 ± 5 min and 85 ± 7 min, respectively. The primary endpoint was achieved by 9% and 12% of cases at 12 and 24 month follow up, respectively. Upper limit skin-to-skin time and missed FPI resulted predictors of the primary endpoint.ConclusionThis standardized workflow resulted in low procedural times and arrhythmias recurrence without compromising the safety.